The Children of Spring Street The Bioarchaeology of Childhood in a 19th Century Abolitionist Congregation - Ellis, Meredith A. B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book examines how the shifts in the early 19th century in New York City affected children in particular. Indeed, one could argue that within this context, that "children" and "childhood" came into being. In order to explore this, the skeletal remains of the children buried at the small, local, yet politically radical Spring Street Presbyterian Church are detailed. Population level analyses are combined with individual biological profiles from sorted burials and individual stories combed from burial records and archival data. What emerges are life histories of children-of infants, toddlers, younger children, older children, and adolescents-during this time of transition in New York City. When combined with historical data, these life histories, for instance, tell us about what it was like to grow up in this changing time in New York City.
1: Introduction -- 2: Sketch of a City -- 3: Hearth and Home: Infants, Birth through 1.5 Years of Age -- 4: Exposures: Toddlers and Younger Children, 1.5-4.5 Years of Age -- 5: Restless Youth: Older Children, 4.5-9.5 Years of Age -- 6: Transitioning: 9.5-14.5 Years of Age -- 7: Deconstructing Childhood. .
Keywords: Archaeology; Physical anthropology; Archaeology; Physical-Biological Anthropology